Penetapan Terutang Pajak Saat Terjadinya Peralihan Hak Atas Tanah dan/atau Bangunan - Alifa Ramadhanty Rachman (UNES Law Review, 2023)
The Indonesian government has promulgated Government Regulation Number 35 of 2023 concerning General Provisions for Regional Taxes and Regional Retributions (refers to PP General PDRD Provisions), which is the implementing provision of Law Number 1 of 2022 concerning Financial Relations Between the Central Government and Regional Governments (hereinafter called as the HKPD Law). This research raises two promblem statements, the determination of tax payable when the rights to land and/or buildings are transferred based on the PDRD General Provisions PP, and the notary's obligations regarding the confidential principle of office in the PDRD General Provisions PP. This research is normative legal research, with a statutory approach and a conceptual approach, where the data analysis is qualitative, carried out through legal science interpretation. The research results show that the determination of what is owed by BPHTB when the rights to land and/or buildings are transferred based on the PDRD General Provisions PP still raises legal concern, both at a theoretical and practical level. The notary's obligation to comply with the confidential principle of office in the PP does not have a basis because the HKPD Law does not regulate this obligation. Hence, this obligation can be overridden